Clinical chorioamnionitis: where do we stand now? - Lukanović, David; Batkoska, Marija; Kavšek, Gorazd; Druškovič, Mirjam (Frontiers in Medicine, 2023)
Intraamniotic infection is an infection resulting in the inflammation of any combination of the amniotic fluid, the placenta, the fetus itself, the fetal membranes, umbilical cord, or the decidua. In the past, an infection of the amnion and chorion or both was dubbed chorioamnionitis. In 2015, a proposal was made by an expert panel that, instead of clinical chorioamnionitis, the name intrauterine inflammation or infection or both be used, abbreviated as Triple I or simply IAI. However, the abbreviation IAI did not gain popularity, and this article uses the term chorioamnionitis. Chorioamnionitis may arise prior to, during, or following labor. It can present as a chronic, subacute, or acute infection. Its clinical presentation is generally referred to as acute chorioamnionitis. The treatment of chorioamnionitis varies widely across the world due to different bacterial causes and the absence of sufficient evidence to support a specific treatment regimen. There are limited randomized controlled trials that have evaluated the superiority of antibiotic regimens for treating amniotic infections during labor. This lack of evidence-based treatment suggests that the current choice of antibiotics is based on limitations in existing research, rather than absolute science. Chorioamnionitis cannot be cured by antibiotic therapy alone without delivery, and therefore it is necessary to make a decision according to the guidelines for induction of labor or acceleration of delivery. When a diagnosis is suspected or established, it is therefore necessary to apply broad-spectrum antibiotics according to the protocol used by each country, and to continue with them until delivery. A commonly recommended first-line treatment for chorioamnionitis is a simple regimen consisting of amoxicillin or ampicillin and once-daily gentamicin. Available information is not sufficient to indicate the best antimicrobial regimen to treat this obstetric condition. However, the evidence that is currently available suggests that patients with clinical chorioamnionitis, primarily women with a gestational age of 34 weeks or more and those in labor, should receive treatment with this regime. However, antibiotic preferences may vary based on local policy, clinician experience and knowledge, bacterial reasons for the infection, antimicrobial resistance patterns, maternal allergies, and drug availability.